Alignment of countries in the Americas with the latest WHO guidelines for hepatitis B virus (HBV) infection: a review - Hugo Perazzo; Estevão Portela Nunes; Sandra W. Cardoso; Valdilea G. Veloso; Beatriz Grinsztejn (The Lancet Regional Health. Americas)
Summary: Evidence is lacking on alignment of current guidance from the Region of the Americas (AMR) countries with the new guidelines for people with hepatitis B virus (HBV) infection published by the World Health Organization (WHO) in March 2024. We gathered the most updated guidance on HBV infection from organisations/societies and seven countries from AMR. Most guidelines were aligned with the new WHO recommendation to treat persons with elevated ALT and HBV-DNA levels ≥2,000 IU/ml or with HIV-coinfection, hepatocellular carcinoma family history, extra-hepatic manifestations, or immunosuppression. The new WHO 2024 guidelines introduced treatment for persistently abnormal ALT in the absence of HBV-DNA, with TDF and/or entecavir as first-line therapy. TDF in pregnant women with high HBV-DNA levels was recommended to prevent mother-to-child transmission (MTCT). These guidelines advised prophylaxis to pregnant women with positive HBsAg where HBV-DNA is unavailable. WHO 2024 and updated guidelines from most AMR countries had simplified and expanded criteria for HBV treatment and MTCT prevention.